Comparison of the Effectiveness of Schema Therapy and Mindfulness on Sexual Coldness and Marital Risky Behaviors - Agha Tehrani, Nayyereh; Bahreinian, Seyed Abdolmajid; Shahabizadeh, Fatemeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This research aimed to compare the effectiveness of schema therapy and mindfulness on sexual coldness and marital risky behaviors.Methods and Materials: This study employed a quasi-experimental design with pre-test and post-test involving two intervention groups. The population consisted of all clients who presented with marital problems at psychology and counseling centers in Isfahan in 2021. Using four questionnaires, including the Halbert Sexual Desire Inventory (1992) and the Risky Marital Behaviors Questionnaire by Zarei and colleagues (2010), 45 couples were selected through purposive sampling and randomly assigned to three groups. The experimental groups received eight 90-minute sessions of schema therapy and mindfulness interventions, while the control group received no such training. After the intervention period, a post-test was administered to all three groups. The obtained data were analyzed using covariance analysis via SPSS statistical software.Findings: The results indicated that the effectiveness of both schema therapy and mindfulness on sexual coldness and marital risky behaviors was significant (P < 0.001). However, no significant difference was found between the mean scores of sexual coldness and marital risky behaviors in the schema therapy and mindfulness intervention groups.Conclusion: It can be concluded that both schema therapy and mindfulness were effective in reducing sexual coldness and marital risky behaviors, and both approaches can be utilized to address psychological problems in couples experiencing marital issues.